The Macroeconomic Determinants of Loan Loss Provision in Chinese Banks - Li, Zhen (2017)
The study explores the relationship between the macroeconomic determinants and the loan loss provision in the three most developed urban agglomerations（the Pearl River Delta urban agglomeration, the Yangtze River Delta urban agglomerations and the Beijing-Tianjin-Hebei urban agglomeration）in China. The study also tests whether capital management, earning management and signaling exist in the banking industry of the three urban agglomerations. To find out the relationship of the independent variables with the loan loss provision, the System Generalized Method of Moments (SGMM) was used to process the 2009-2015 data from 130 banks. The data come from two sources: databases (Fintect-connect, Bankscope) and some reports from banks and the government. The research findings are as follows. Banks use the loan loss provision to manage the capital adequacy ratio in the Pearl River Delta urban agglomeration and the Yangtze River Delta urban agglomeration. Only in the Yangtze River Delta urban agglomerations the loan loss provision shares the significant relationship with earnings. Procyclicality exists In the Yangtze River Delta urban agglomeration and the Beijing-Tianjin-Hebei urban agglomeration. In China, the loan loss provision almost has no signaling function. It is recommended that the Chinese government should insist in the dynamic provision system in order to reduce the impact of procyclicality.